An introductory guide to evaluative reporting in forensic science. (29th July 2019) - Catoggio, D.; Bunford, J.; Taylor, D.; Wevers, G.; Ballantyne, K.; Morgan, R.
ABSTRACT: Evaluative reporting provides a balanced approach to evidence interpretation. The use of evaluative reporting in forensic DNA analysis is common practice and well understood in Australia and New Zealand. However, it is less common and perhaps less understood in the pattern and trace evidence areas. Recent publications, such as the 2015 'European Network of Forensic Science Institutes (ENFSI) Guideline for Evaluative Reporting in Forensic Science', have prompted discussion in Australia and New Zealand about the benefits and risks of expanding its application in forensic science. To aid discussions and build a common understanding of evaluative reporting, the Australia New Zealand Policing Advisory Agency National Institute of Forensic Science (ANZPAA NIFS) convened a project working group to create 'An introductory guide to evaluative reporting'. The guide covers terminology and uses examples to illustrate the concepts. It also provides advice on the implementation of evaluative reporting in forensic science disciplines. This article provides an overview of the project, and the methodology and thinking behind the development of the guide and its associated fact sheet and process poster.